Strategic Quality Control of Hotel Services - Misra, Lalat Indu; Samal, Ansuman; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Performance and quality control have become critical strategic considerations in achieving sustainability and productivity on the aggressive tourism industry, in conditions of increasing global rivalry, consumer demands and requires. Every serious "upper" hotel management, with an established mission, dream and priorities, will identify a "unique approach" to improve the quality of hotel services by way of "structural quality improvement initiatives," which have become a major factor in the hotel business. With the creation, implementation and operation of a "special program" for improving the quality of hotel facilities, hotel management can have a positive impact on growing customer satisfaction and human resources, raising the hotel's profitability and market strength, streamlining the operating costs and maximizing the hotel's credibility and valuation on the challenging tourism sector. This paper discusses about the latest trends and changes in modern hotel industry and most importantly, the impact of quality of hotel services and its direct impact on tourism industry.